Language teachers as educators for sustainability in Finland – Factors influencing teachers’ perception of their agency - Kuusalu, Salla-Riikka; Patzelt, Mareen; Maijala, Minna (Walter de Gruyter GmbH, 2026)
Agency enhances teachers’ professional development and influences their capability of integrating education of sustainable development (ESD). This study focuses on language teachers’ agency as educators for sustainability both at the institutional system level and in language classes. We investigate how language teachers perceive their agency in ESD, how their experiences affect their perception of agency in ESD, and how they use their agency in the integration process. Data were gathered with individual semi-structured interviews of six language teachers in Finland and analysed using a modified inductive paradigm model. The teachers considered having agency in ESD when they received enough support, had sufficient guidance, could affect teaching materials, and had proactive students. Teachers had many operational strategies for solving the challenges in integrating ESD, but negative experiences and lack of support were reflected as a diminished capability for agency and decreased capacity to integrate ESD.